Growth performance and nutrient digestibility of broilers fed different type of diets and feed additives - Nalle, C. L.; Helda, H.; Toelle, N.; Mawaddah, U. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
This research aimed to evaluate the nutrient digestibility and the growth performance of broilers fed a different type of diet (TD) and feed additives (FA). A total of 264 day-old chicks (male, Lohmann) were randomly distributed into 24 pens (11 birds/pen). The experiment was designed by using a 2 x 4 factorial completely randomized design with the main factors TD and FA. The result shows that TD x FA interaction was significant (p<0.05-0.001) for feed intake (FI) and body weigt gain (BWG) of starter broilers. The TD, FA, and TD x FA affected (p<0.01-0.001) growth performance (GP) of growing broilers. TD and TD x FA interaction affected liver weight and the length of proventriculus and gizzard (p<0.05 to 0.001). Except for starch, the TD did not affect (p>0.05) nutrient digestibility (ND) and energy values (EV). Except for crude protein, FA did not affect (p>0.05) on ND and EV. The TD x FA interaction did not affect ND and EV. TD affected (p<0.05–0.001) on FI and BWG)of starter broilers. Except for day 7, FA influenced (p<0.01–0.001) FI and BWG of starter broilers. In conclusion, 1) The addition of Synbiotics and Allzyme SSF-E on Rice bran-sago diet (RSD) improved the GP of birds; and 2) The complex and multi enzymes work well in the rice bran-sago diet  3) RSD produced better growth performance of broiler starter.